Breast Cancer Susceptibility Gene 1 (BRCA1) And Breast Cancer - Lakhotia, Smita (2009)
Breast Cancer susceptibility gene 1 (BRCA1) & Breast Cancer Breast cancer is one of the most common malignancies affecting women worldwide. About 5-10% of all cases are estimated to be familial. Mutations in the BRCA1 (Breast Cancer susceptibility gene 1) gene account for about 15-20% of inherited breast cancer cases and 60-80% of families predisposed to both breast and ovarian cancer. BRCA1 mutations also result in susceptibility to early-onset breast and ovarian cancer. The human BRCA1 gene encodes a multi-domain 1,863 amino acid nuclear protein that is expressed in a wide variety of adult human tissues. The N-terminal end of BRCA1 contains a RING-finger domain. Exon 11 of BRCA1 contains two nuclear localization signals towards its N-terminal for targeting BRCA1 to the nucleus. The carboxyl terminus contains two BRCT (BRCA1 C-terminal) domains and a transcriptional activation domain. This study was carried out to functionally characterize BRCA1 and to find out the percentage in which BRCA1 gene is mutated in Indian familial breast and/or ovarian cancer families. The work has been divided into three sections: 1. Identification & characterization of a BRCA1 Associated Protein 2 (BAP2). 2. Germ-line BRCA1 mutation Analysis in Indian Breast and/or Ovarian Cancer Families. 3. Characterization of a novel missense mutation (E116K) in BRCA1. BRCA1 is known to interact with large number of proteins and is involved in various cellular functions like tumorigenesis, transcription, DNA damage repair, cell-cycle control, ubiquitinylation, genetic stability, cell growth and apoptosis. The interacting partners of BRCA1 have given a lot of clue about the functions of this complex protein. In the first project, we used the yeast two-hybrid system to identify novel interacting proteins of BRCA1. We used the 1-500 amino acid region of BRCA1 as bait in library screen and picked up a novel clone (clone 89) showing interaction with BRCA1. Clone 89 contains approximately 2.3 Kb long cDNA sequence. Using the nucleotide blast search, we obtained a full-length cDNA of approximately 5.4 Kb (KIAA0657) that is located on chromosome 2, 2q36.1 region. We have named this new protein BRCA1 Associated Protein 2 (BAP2). Translation of this coding sequence gave a protein that has homology to Titin protein. This protein, which has 1,236 amino acids, contains 9 Immunoglobulin like domains. The homologues of this protein exists in many other organisms but the function is not known. We have confirmed the interaction between BRCA1 and c89 using in vitro GST pull-down assay. We have studied the influence of BAP2 on various functions of BRCA1 like transcription, colony suppression and cell cycle. In the transcription assays, BAP2 activated p21 promoter activity perhaps by using endogenous BRCA1 as simultaneous ectopic expression of truncated BRCA1 (containing aa 1-500) abolished this activity. Further, BAP2 also increased the ability of BRCA1 to activate p21 promoter suggesting that BAP2 may act as a co-activator of BRCA1 functions. Surprisingly, we observed that BAP2 inhibited p53-mediated transcription both in the absence and presence of BRCA1. BAP2 failed to inhibit colony growth by itself as well as in combination with BRCA1. In the cell-cycle study, we found that BAP2 did not have any significant effect on cell cycle profile by itself. However, it drastically augmented the G2/M arrest mediated by BRCA1. Thus we conclude that we have identified a novel interacting protein of BRCA1 that regulates certain functions of BRCA1. Detection of mutations is of central importance in the study of genetic and malignant diseases. Mutation detection helps us in understanding the protein structure, function and expression. More than that, it is also important for pre-symptomatic/antenatal diagnosis, confirmation of the genetic cause of the disease and the mode of inheritance of a disease in a particular family, the prediction of clinical phenotype and the potentiation of diagnostic analysis in the case of families with incomplete pedigrees or with new mutations. Therefore, the importance of direct mutation analysis cannot be understated. The second project deals with screening of mutations in BRCA1 gene in 50 familial breast and/or ovarian cancer families using the technique of Conformation Sensitive Gel Electrophoresis (CSGE). CSGE can be used to detect mismatches in DNA heteroduplexes that contain one strand of wild type and one strand of mutated DNA. In a collaborative study with Kidwai Memorial Hospital for Oncology, Bangalore, we screened 50 families suffering from breast and/or ovarian cancer. We detected 13 mutations in this study out of which 3 are novel and 10 have already been reported earlier (Breast Information Core). All the mutations obtained in our study result in truncation of the BRCA1 protein either because of non-sense mutation or frame-shift mutation. Interestingly, 8 of the mutations detected are 185delAG mutations – the most commonly occurring mutation in Ashkenazi Jewish population. From this study, we conclude that BRCA1 is mutated in 26% of familial breast and/or ovarian cancer cases in India. Genetic testing in individuals with family history of breast, ovarian or both has become very common. It is difficult to interpret the result of genetic screen if a DNA change in the gene does not result in truncation of the protein. Rare missense changes of unknown functional and pathogenic significance are called unclassified variants. It is important to study the functional implications of these unclassified variants in order to determine the risk associated with the presence of such variations. The third project deals with characterization of one such missense variation. In an earlier mutation analysis study for BRCA1 gene in breast cancer samples, we found a novel missense variation resulting in Glu116Lys (E116K) change. In order to determine if this variant is a disease associated missense mutation or a benign sequence alteration; we introduced this variation into full length BRCA1 cDNA and studied its effect on the known functions of BRCA1, namely, transcription, colony suppression and cell cycle. We found that E116K is defective for activating transcription. However, it continued to inhibit growth in colony formation assay and arrest cells in G2/M phase of cell cycle. We conclude that E116K mutation results in loss of transactivation function of BRCA1 but has no effect on colony formation and cell cycle regulation; thus it can be categorized as a novel missense mutation.